Recommendation of Heat Exchanger as Refrigerant Cooler through Mass Balance Calculation in LNG Plant Process - Eky Novianarenti; Heroe Poernomo; Erlinda Ningsih; Imaniah Sriwijayasih; Arrad Ghani Safitra (Universitas Negeri Padang, 2024)
The liquefaction unit is a process unit for processing the desired product from the gas phase to the liquid phase. The purpose of this unit is to facilitate the transportation process with the help of refrigerants. The disadvantage of this unit is that the heat transfer is less than optimal. In addition, this study can also maximize the storage system because it can reduce the specific volume of gas up to 1/600 times to increase energy efficiency in the LNG Plant. The potential for various options to increase the efficiency of the liquefaction cycle is tried to be calculated in this study. The calculation method between the mass balance and energy balance obtained the results of the design calculation that the type 2-4 heat exchanger, Carbon steel material, area 1023, 35m2, Rd 0.001-hour ft2 °F / Btu can be concluded that the design of the heat exchanger is safe and recommended.